1998
DOI: 10.1023/a:1006075312688
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The sedative and analgesic effects of medetomidine were evaluated in heartworm-infected (HW+) and uninfected (HW-) beagle dogs by intravenous (IV) and intramuscular (IM) administration of 30 micrograms/kg and 40 micrograms/kg doses, respectively. Posture, response to noise and the pedal reflex were monitored. A procedure for mock radiographic positioning was performed to evaluate its overall clinical use. Observation times were 0, 15, 30, 60, 90, 120 and 180 min. In addition, the times from injection until the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The acute and long lasting decrease in respiratory rate after treatment with medetomidine was also observed by Clarke and England (1989), England and Clarke (1989a, b) and Räihä and others (1989a, b), and was not dose related, although Young and others (1990) did report a dose‐related decrease. The intermittent dyspnoea, interspersed with apnoea, was also recorded by Clarke and England (1989) and the observation of unchanged blood gas values agrees with observations by Pettifer and Dyson (1993) and Venugopalan and others (1994). In contrast there were adverse effects on respiration and the blood acid/base status after treatment with xylazine plus 1‐methadone, which in half the dogs caused severe panting.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The acute and long lasting decrease in respiratory rate after treatment with medetomidine was also observed by Clarke and England (1989), England and Clarke (1989a, b) and Räihä and others (1989a, b), and was not dose related, although Young and others (1990) did report a dose‐related decrease. The intermittent dyspnoea, interspersed with apnoea, was also recorded by Clarke and England (1989) and the observation of unchanged blood gas values agrees with observations by Pettifer and Dyson (1993) and Venugopalan and others (1994). In contrast there were adverse effects on respiration and the blood acid/base status after treatment with xylazine plus 1‐methadone, which in half the dogs caused severe panting.…”
Section: Discussionsupporting
confidence: 89%
“…These observations are in general in agreement with α 2 ‐effects on cardiovascular function as described by Clarke and England (1989), Lombard and others (1989) and Vainio (1989). Experimental and clinical studies using doses calculated on the basis of body surface area have shown that these substance‐specific cardiovascular responses, even in dogs with severe (heartworm‐related) cardiac insufficiency did not result in life‐threatening problems (Venugopalan and others 1994, C. L. Tyner, B. J. Woody, J. S. Reid, E. P. Chafetz, H. A. Lederer, F. F. Norton, W. Jöchle, unpublished observations). Studies in dogs with instruments implanted in their hearts have shown that these typical α 2 ‐adrenergic effects are fully established with an intravenous dose of 10 μg/kg medetomidine, reach a maximum with a dose of 30 μg/kg, and are prolonged with higher doses (D. Franklin, personal communication).…”
Section: Discussionmentioning
confidence: 99%